Cross leg Flap - V. N. Gupta; S. S. Sethi (Indian Journal of Plastic Surgery)
A serics of 15 cases of cross leg ilap have been presented with the donor area from the medial surface of the leg and the anterior surface of the thigh, because of the better vascularity of these areas. An anatomical basis of the vascularity of the medial surface of leg is discussed, and the importance of the preservation: of these cutaneous branches of the posterior tibial arlery, is impressed upon.